Effectiveness of Wuluh Starfruit Leaf (Averrhoa bilimbi Linn) Extract on The Growth Streptococcus mutans In Vitro - Riza, Ahyar; Hayati, Fitrah; Siregar, Indra Basar; Oes, Abdullah (Dentistry Faculty, 2023)
Background: Starfruit (Averrhoa bilimbi Linn) contains vitamin C, flavonoids, tannins, and triterpenoids. This active compound is reported to prevent the growth of bacteria, including Streptococcus mutans. Objective: This study aims to determine the effectiveness of starfruit leaf extract (Averrhoa bilimbi Linn) in inhibiting Streptococcus mutans. Method: This type of research is true experimental with a post-test-only control design, where this research uses the Kirby-Baur diffusion method with samples of Streptococcus mutans bacteria and uses wuluh leaf extract with concentrations of 50%, 25%, 12.5%, 6 .25%, 3.125%. And DMSO solution as a negative control. Results: The formation of a clear zone shows the ability of starfruit leaf extract to inhibit the growth of Streptococcus mutans, with an average inhibitory diameter of 12.05 0.7188, 9.50 0.3464.8, 65 0.2380, 7.80 0.4546, 6.78 0.8016. Conclusion: Based on the research results, it can be concluded that Averrhoa bilimbi Linn can inhibit Streptococcus mutans.